PERAN BIMBINGAN DAN KONSELING DALAM PENINGKATAN KOMUNIKASI EFEKTIF PADA GENERASI Z DI PANTI ASUHAN MANDE KANDUANG - Cindy Riswana Putri; Dodi Pasila Putra (CV. ADIBA AISHA AMIRA, 2024)
In this study, most generation Z were not able to communicate directly due to a lack of self-confidence and ineffective communication. Communication is an important and necessary tool in everyday life to establish relationships with other people. Communication is considered important for generation Z, because they, as the future generation, must understand how to communicate effectively among the general public and must be able to answer questions spontaneously. Currently, generation Z has a close relationship with technology, the need to depend on the internet both in the social world, education, knowledge of something that makes them unable to communicate in the real world. The purpose of this research is information regarding the role of BK in improving effective communication in generation Z. The research method used is descriptive qualitative. So it was concluded that collaborating with the orphanage administrators by reviewing the positive things that were expected to happen optimally. The data collection techniques used were observation and interviews, where the author interviewed orphanage administrators regarding their communication skills in increasing effective communication. In analyzing the data, data reduction and data verification were carried out by summarizing the data found in the field. Guidance and counseling services should be directed at equipping generation Z with superior character by utilizing information and communication technology so that they can lead them towards a bright future. From this, it can be seen that development guidance and counseling will play a very important role in facing and preparing a quality generation Z